Determination of Atmospheric Gusts Using Integrated On-Board Systems of a Jet Transport Airplane—3D Problem - Piotr Szwed; Paweł Rzucidło; Piotr Grzybowski; Krzysztof Warzocha (Applied Sciences)
The importance of gust detection and its impact on flight is a broad and critical subject, particularly in the context of flight safety. When a gust is detected early through appropriate methods, the pilot can adjust the aircraft’s flight state accordingly, thereby reducing the risk associated with adverse atmospheric conditions. Without timely intervention, such conditions may compromise safety margins. If early detection is not achieved, the time available for an effective response is significantly reduced. This study investigates state-of-the-art gust detection methods, with a particular focus on their relevance during the final approach phase of flight. A theoretical framework is developed, leading to the formulation of a novel gust detection method. The proposed approach was tested under simulated conditions using an experimental setup comprising both software and hardware components. The simulation environment modelled rapid changes in wind conditions affecting an aircraft, enabling the validation of the method’s capability to estimate gust characteristics. The final analysis evaluates the method’s accuracy using simulation-derived data and discusses its performance, including identified limitations. The findings contribute to the development of more robust gust detection systems and support ongoing efforts to enhance flight safety, particularly during critical flight phases.